Communication Strategy @dialogindocirebon on the Youtube Platform: Digital Transformation and Audience Expansion - Anwar, Saiful; Khoirunnisa, Marhamah; Editya, Afrins; Wihayati, Welly (Pusat Publikasi Nusantara, 2024)
YouTube is a social media platform that facilitates video sharing and watching by offering a wide range of content, including movies, video trailers, and user-generated videos, all at no cost. One of the youtube channels that provides content about information and entertainment is @dialogindocirebon. This study examines the digital transformation of the YouTube platform in expanding the audience with thousands of subscribers on Channel @dialogindocirebon through its communication strategy. This study uses a qualitative descriptive research design. Apply purposive sampling as a data collection method or for the selection of research samples. Non-participant observation and in-depth interviews were used to collect data. The research findings were obtained through the application of qualitative data analysis techniques. The result of the research is that the strategy used by the youtube channel @dialogindocirebon is to divide the market segmentation by creating sub-sub channels according to the target market city.